Antioxidant effects of whey proteins in vitro [Süt serumu proteinlerinin in vitro koşullardaki antioksidan etkileri] - (:unkn) unknown (My University, 2011)
Whey is the liquid part which is responsible for the therapeutic effects of milk. Whey is a product of cheese manufacture and is rich in milk serum proteins. This by-product is powdered and used in the nutritonal industry. In recent years, increasing number of studies clarifying the multiple therapeutic effects of whey have appeared. Its protective effects on free radical damage and anticarcinogenic effects are the major ones among other beneficial effects. In this study, we have investigated preventive effects of whey proteins against lipid and protein oxidation of serum in vitro. We have used whey powder and raw liquid whey in our experiments. We determined their antioxidant effects against lipid and protein oxidation in human serum samples oxidized by CuSO4. Sulfhydryl (-SH) groups of heated and non-heated whey proteins was measured using a modification of the Ellman assay, lipid peroxidation by TBARS and Diene Conjugation methods and protein oxidation by protein carbonly method. Bradford Method was used in protein measurements of samples. In our in vitro experiments, we observed that the reactive sulphydryl group content is related to the antioxidant effects of whey proteins and -SH content of whey powder is higher than in raw milk serum. Therefore, whey powder has a stronger antioxidant effect than raw milk serum.
Keywords: Antioxidant; Lipid peroxidation; Whey; Whey proteins